Adillatu al-Nahw Fi Syarh Kitab al-Kawakib al-Durriyyah 'Ala Mutammamah al-Ajrumiyah wa Atsar Isti'maluha 'Ala Fahm al-Qowaid al-Nahwiyah - Asrina Asrina; Arbonas Lubis (Arabiyatuna : Jurnal Bahasa Arab, 2019)
The objectives of this study were to find out the syntax evidence (adillah al-nahwu) in the book Syarh Kitab al-Kawakib al-durriyah ala Mutamammimah al-Ajrumiyyah, how to use the evidence of syntax (adillah al-nahwu) in its book, and what are the effects of syntax evidence (adillah al-nahwu) in grammatical rules. The purposes of the research are to find out the syntax evidence (adillah al-nahwu) in the book Syarh Kitab al-Kawakib al-durriyah ala Mutamammimah al-Ajrumiyyah and to explain the evidence of syntax (adillah al-nahwu) found in its book, and to know the effects of the evidence of syntax (adillah al-nahwu) in the grammar rules. This research used library research where the data were collected through document analysis. The results of the research that the most adillah that used Ar-Ruainiy were sama or naql, ijma, and Hadith. Dalil al-Sama of the Qur'an used in the book Syarh Kitab al-Kawakib al-Durriyah ala Mutamammimah al-Ajrumiyyah were 102 evidences, dalil of Hadith were 12 evidences, dalil of the words of the Arabs were 60 evidences, 1 dalil of ijma , and 4 dalil of istishab al-hal. The syntax evidence (adillah al-nahwu) in the book Syarh Kitab al-Kawakib al-Durriyah ala Mutamammimah al-Ajrumiyyah affect on availability for the understanding of the grammar rules.